Improving management performance in rapidly changing organizations / Mahathir Mahali and Junaidah Jamaluddin - Mahali, Mahathir; Jamaluddin, Junaidah (Universiti Teknologi MARA Cawangan Pahang, 2003)
If we were not for change, a manager's job would be relatively easy. Planning could be so simple because it is based on historical events where tomorrow would be no different from today (Robbins et aI., 1999). In addition, decision-making would be very streamlined because the result of every alternative taken in decision-making could be predicted with almost certain accuracy. However, this is not the way things work today's environment is full of uncertainty, market changes, changing workforce demographics, political and also social pressures and mostly 'certainly advancement in technology make today's organization one constant changes (Savery et aI., 2000). Organization in global market place will therefore continues to experience tremendous change. Organizational leaders thought change was an event (Frohman, 1997). However, change is now viewed as an ongoing process triggered by multiple variables (Grieves, 2000). Managers at all levels, but more specifically those at the middle level, must be constantly being reminded of their role and their influence is respect to organizational performance. Leading organizations spend 20 percent of effort on formulating and 80 per cent on the implementation of change and the benefits are accrued from the ability to embrace change more quickly and effectively than competitors (Samson et aI., 2000). With the scenario, we can say that today's competitive environments require organizational change; organizational change requires effective managerial performance; effective managerial performance requires appropriate skills and behavior. Appropriate skills and behavior development are facilitated through appropriate and effective management development activities. This paper, therefore, discusses and offers recommendations about how to improve current management performance in rapidly changing organizations.